Edaphic attributes and loss of soil and nutrients according to the management systems for horticultural crops - Freitas de Souza, José Mário Piratello; Anjos, Lúcia Helena Cunha dos; Pereira, Marcos Gervasio; Guareschi, Roni Fernandes; Gaia-Gomes, João Henrique (Comunicata Scientiae, 2018)
The effects of conventional tillage (CT), level cultivation (LC), minimum cultivation (MC) and a plot without a cover crop (WC) in the contents of soil nutrients (P, K, Ca and Mg), total organic carbon (TOC), bulk density (Bd), soil water infiltration rate (BIR) and losses of TOC and nutrients (P and K) by erosion were evaluated in areas with the cultivation of horticultural crops. Wischmeier plots were installed in an Oxisol with 30% of slope. Soil samples were collected at 0.0-0.05 and 0.05-0.10 m depths to physical and chemical characterization. The WC plot reduces soil SWIR values and lead to a higher losses soil, TOC and macronutrients (Ca, P, Mg and K). The CT resulted in higher losses of soil, TOC, P and K by erosion, contributing to reduce the TOC, P, Ca, Mg and SWIR of the soil. The MC was the most indicated management, since it helps to reduce losses of soil, TOC, P and K by erosion, and increase the TOC, BIR, P, K, Ca and Mg of the soil. The LC when compared to the CT reduces the losses of soil TOC, P and K by erosion, and increase the BIR values.